Carbonate concretions in an ice-contact delta, Skarmunken, Ullsfjord, northern Norway - Amundsen, Mats (UiT Norges arktiske universitet, 2017)
At Skarmunken, a small village south of Ullsfjord, northern Troms, Norway, an outcrop containing carbonate concretions have been investigated. From sedimentary logging, five facies (facies A-E) have been classified by their grading and composition. Depositional data from logs, maximum pebble size (MPS) and earlier investigations suggests an ice-contact delta. TOC/TS data have revealed a dominantly nonmarine depositional environment for the lower half of the outcrop, with one occurrence of marine environment. The occurring carbonate concretions is indicated to have formed in two different processes, where the stratabound concretions are suggested to have formed by local buried carbon sources in the sediments and the carbonate concretions located in sand injections are suggested be the result of fluid migration. The precipitation processes of the carbonate concretions are indicated to be from both hydrocarbon oxidation and oxidation of buried carbon. Environmental data and the local geology suggest a biogenic carbon source for the precipitation of the carbonates. Carbonate concretions samples revealed one main morphology, horizontal - vertical pipe concretions. Additional investigated morphologies were horizontal-subvertical intergrown pipes with plate surfaces, chimneys, blocky boulder and spherulites concretion. Thin section analyzes of the concretions suggests calcium carbonate cementation and a trend of channelized cementation paths. The carbonate concretions were commonly observed to accompany the extensive sand injections in the area, where the sand injections are indicated to be the result of fluidization of a fine-grained sand and mud sequence, caused by rapid sediment deposition and glacial compaction. The occurrence of carbonate concretions inside the sand injections, thin section analysis and concretion morphologies indicate fluid migration control over the distribution of the carbonates and the concretion morphology. Observations of the sand injections and carbonate concretions behavior in the ...